Risk Factors Associated with Hypertension Among Adults Aged 19-64 Years in Ohoijang Watdek, Southeast Maluku - Rahanra, Sartika Riry; Asmin, Elpira; Irwan; Kailola, Nathalie; Haq Hataul, Is Asma'ul (Sriwijaya Journal of Medicine, 2025)
Hypertension is a serious condition that increases the risk of cardiovascular diseases such as coronary heart disease, heart failure, stroke, kidney failure, and other complications. This study aimed to identify risk factors associated with hypertension in the working area of the Ohoijang Watdek Public Health Center. A quantitative analytic method with a cross-sectional design was used. A total of 127 respondents aged 19–64 years, selected through convenience sampling, participated in the study. Univariate analysis described respondents' characteristics, and chi-square tests examined associations between variables. Most respondents had stage 1 hypertension (32.3%), were aged 36–45 (29.9%), female (59.1%), non-smokers (62.2%), non-alcohol consumers (73.2%), had type 1 obesity (26%), and engaged in moderate physical activity (35.4%). Significant associations were found between hypertension and age (p=0.001; r=0.402), family history (p=0.028; r=0.195), smoking (p=0.014; r=0.217), alcohol consumption (p=0.012; r=0.224), and physical activity (p=0.002; r=0.320). Gender (p=0.256) and nutritional status (p=0.440) showed no significant relationship. The study concludes that age, family history, smoking, alcohol consumption, and physical activity are significantly associated with hypertension, while gender and nutritional status are not.